2014
DOI: 10.5125/jkaoms.2014.40.6.291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human bone morphogenetic protein-2 on bisphosphonate-treated osteoblasts

Abstract: ObjectivesBisphosphonate-related osteonecrosis of the jaw (BRONJ) is a side effect of bisphophonate therapy that has been reported in recent years. Osteoclastic inactivity by bisphosphonate is the known cause of BRONJ. Bone morphogenetic protein-2 (BMP-2) plays an important role in the development of bone. Recombinant human BMP-2 (rhBMP-2) is potentially useful as an activation factor for bone repair. We hypothesized that rhBMP-2 would enhance the osteoclast-osteoblast interaction related to bone remodeling.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Recombinant human BMP-2 (rhBMP-2), a bone healing activating factor, exhibits osteogenic effects and has been used widely in dental clinics. Through a previous study, we know that rhBMP-2 and LLLT have stimulating effects on BP-treated osteoblasts15. In this study, we investigated the synergic effect of rhBMP-2 and LLLT on BP-treated osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human BMP-2 (rhBMP-2), a bone healing activating factor, exhibits osteogenic effects and has been used widely in dental clinics. Through a previous study, we know that rhBMP-2 and LLLT have stimulating effects on BP-treated osteoblasts15. In this study, we investigated the synergic effect of rhBMP-2 and LLLT on BP-treated osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of literature studying the effects of the rhBMP2 on nonmature bone cells. One study using fetal osteoblasts did establish rhBMP‐2 can recover M‐CSF expression after bisphosphonate treatment . As M‐CSF is also important in the monocyte/macrophage lineage, specifically for proliferation and differentiation, it is possible rhBMP‐2 may act directly on macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…One study using fetal osteoblasts did establish rhBMP-2 can recover M-CSF expression after bisphosphonate treatment. 41 As M-CSF is also important in the monocyte/macrophage lineage, specifically for proliferation and differentiation, it is possible rhBMP-2 may act directly on macrophages. Thus, much more work on the effect of rhBMP-2 on macrophages is necessary to completely rule out this specific cell population as being implicated in the heightened inflammation associated with the clinical rhBMP2 dose.…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are part of the TGF-β superfamily, which includes 43 members. It was previously demonstrated that BMPs could induce mesenchymal cells to irreversibly differentiate into cartilages and bone cells in vivo (5)(6)(7). Additionally, the wingless-type mouse mammary tumor virus integration site family is a class of Wnt gene-encoded secretory glycoproteins.…”
Section: Introductionmentioning
confidence: 99%